The Relationship Between the Characteristics and Level of Knowledge of Parents about Kawasaki Disease - Rodiyanah, Rodiyanah; Mustajidah, Mustajidah; Permaini, Titi; Haryati, Haryati; Alviani, Desi Rusiana (Indonesian Journal of Global Health Research, 2023)
Data obtained from RS X, pediatric patients with Kawasaki disease within three years (2019 – 2021) were 1,705 cases, where the average visit for the last 3 months was 140 cases. The purpose of this study was to determine the relationship between the characteristics and level of knowledge of parents about Kawasaki disease in RS X. The design of this study was to use a cross-sectional correlation analytical design with the type of research used quantitative associative research. In this study, the independent variable is the characteristics of parents including gender, age, education level, and employment status while the dependent variable is the level of knowledge. 4 variables namely gender (p-value = 1,000), age (p-value = 1,425), education (p-value = 0,326) and employment status (p-value = 1,000) The conclusion of this study is that it cannot prove there is an association with the level of parental knowledge about Kawasaki disease in RS X.